2007
DOI: 10.1108/10662240710737013
|View full text |Cite
|
Sign up to set email alerts
|

Network externality and future usage of Internet services

Abstract: Purpose-The purpose of this paper is to investigate different effects of three network externality factors, i.e. local network size, network strength, and total network size, on online messenger, online community, chat room and e-mail services. Design/methodology/approach-In the paper hypotheses are tested with a regression model using a survey data collected from 107 MBA students at a business school in South Korea. Findings-The paper finds that the three network externality factors have different effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Network externality is defined as changes in benefits that a consumer derives from goods when the number of people consuming the same kind of goods changes [54]. In consumer product market, network externalities play an important role, as the effect derived from network externalities can bring about more benefits and profits for companies [55]. For IoT-based wearable fitness trackers, more benefit is achieved as more users adopt the device.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Network externality is defined as changes in benefits that a consumer derives from goods when the number of people consuming the same kind of goods changes [54]. In consumer product market, network externalities play an important role, as the effect derived from network externalities can bring about more benefits and profits for companies [55]. For IoT-based wearable fitness trackers, more benefit is achieved as more users adopt the device.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is recognized as a core factor that determines the continuance use of an information system. For instance, Sung and Hahn (2007) found that user satisfaction contributes to the success of a network service. Assensoh- Kodua and Lekhanya (2014) showed that satisfaction is one of the salient determinants of continuance intention in the SNSs context.…”
Section: User Satisfactionmentioning
confidence: 99%
“…Our results also showed a significant direct influence of social interaction context on discontinuance intention. Social interaction context is determined by a user's perception of network strength, which is based on the quality of interactions among users within the network (Chun and Hahn, 2007; Quan-Haase and Young, 2010). This individual-level network property has been discussed to improve user cohesion or intimacy with other users (Granovetter, 1973; Keyton and Springston, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al , 2019), this study conceptualizes two SNS-specific contextual factors, that is, social interaction context and platform service context. First, as a social context, social interaction context is associated with the frequency/time and the strength of personal network on SNS (Chun and Hahn, 2007; Wang and Chen, 2012). Since a social interaction condition is formed through interactions with other users within the SNS, it drives the user's social capital regarding his/her use of the SNS (Ellison et al , 2007).…”
Section: Theoretical Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation